I believe it would be (b) (-2,1)
If x + 4y = 6 and you subst. -x+3 for y, you get x + 4(-x+3) = 6.
Then x - 4x + 12 = 6, or -3x = -6, or x = 2. Since y = -x+3, here y = -(2)+3 = 1.
Thus, the solution to this system of linear equations is (2,1).
Answer:
12 + 6 have a good day
Step-by-step explanation:
X6 – 9x3 + 8 = 0
let u = x^3
u^2 - 9u + 8 = 0
(u-8)(u-1) = 0
u = 1,8
back substitute
1 = x^3
8 = x^3
<span>x = 1 , 2</span>
Answer:
A) 11/36
Step-by-step explanation:
x + 4/9 = 3/4
get a common denominator of 36 (4*9 = 36)
x + 4/9 * 4/4 = 3/4 * 9/9
x + 16/36 = 27/36
subtract 16/36 from each side
x + 16/36 - 16/36 = 27/36 -16/36
x = (27-16)/36
x = 11/ 36